Guía docente para orientar el desarrollo de la sexualidad infantil para niños y niñas del primer año de educación básica del cecib Marco Rodríguez de la comunidad Santa Rosa de la compañía, de la parroquia Ayora del cantón Cayambe. - Carrión Sanchéz, Adriana Paola (2013)
Sexuality is a central aspect of being human throughout this life. It covers sex, as identities and gender roles, eroticism, pleasure, intimacy, reproduction and sexual orientation. You live and expressed through thoughts, fantasies, desires, beliefs, attitudes, values, behaviors, practices and impersonal relationships. In the same way that society is influenced by the interaction of biological, psychological, social, economic, political, cultural, ethical, legal, historical, religious and spiritual, this being an essential condition of the people, which must be treated with greater emphasis on children, since they also have sexual and emotional first experiences with fire mark the life of a subject.